Gradual changes in model shape affect egg-directed behaviours by parasitic shiny cowbirds Molothrus bonariensis in captivity - Crudele, Ignacio (2023)
Eggs are critically important for avian reproduction as all birds are oviparous. Accordingly, the recognition and care of own eggs represent the cornerstones of avian breeding, whereas the elimination of foreign objects, including brood-parasitic eggs and non-egg items from the nest are known to also increase fitness by refocusing incubation effort on the parents' own eggs. But egg recognition also plays a role in some avian obligate brood parasites' reproductive strategy through the pecking of already present eggs in the hosts' clutch to reduce nestmate competition with the parasite's own hatchling. Here we tested egg shape recognition in this parasitic egg-pecking context by exposing two different series of 3D printed models to captive obligate brood-parasitic shiny cowbirds (Molothrus bonariensis) in artificial nests. Natural egg-shaped models were pecked more often compared with increasingly thinner models, but there was no effect of increasing angularity on pecking rates, implying that a natural, rather than an artificial, range of variability elicited adaptive responses from parasitic cowbirds.